PENINGKATAN KREATIVITAS GERAK MELALUI KEGIATAN TARI PENDIKAN BERBASIS CERITA (TARITA) - JUNIASIH, INDAH (Jurnal Pendidikan Usia Dini, 2015)
Abstract: This research purposes is to obtain empirical data about educational dance activity based on story (TARITA), in an effort to improve early childhood’s creative movement. The method that used in this research is a action research. In this study.These research through four stages activities, which are planning, action, observation and refelection. Action in this research was conducted in two cycles with a total of 12 times meetings. Sources of data in this study were students who join RA Robbani dancing extracurricular activities. The collection of data is done through the rubric, observation, interviews, and documentation study. The results showed that TARITA activities can improve children's creative movementthat on a pre-cycle was 30.72%. Then increased to 54.4% at the end of the first cycle and continued to increase to 77.4% at the end of the second cycle. It shows that it has been achieving the research minimal target of 71%. The research concludes that TARITA become one of the good alternative methods for improving early childhood creative movement. Keyword: Educational Dance, Story Teling, dan Creative Movement